EKSPLORASI ETNOMATEMATIKA MAKANAN TRADISIONAL MELAYU PESISIR MANDAILING NATAL SEBAGAI SUMBER BELAJAR MATEMATIKA - Putri, Nelliani; Asrul (Euclid, 2024)
This qualitative research uses an ethnographic approach by utilizing the researcher as the main instrument. Researchers play an active role in data collection, data collection techniques include observation, interviews and documentation. The results of the research obtained an analysis of the manufacturing process and product results regarding the shape of the food, it is known that the traditional Malay coastal food of Mandailing Natal has geometric shapes in the form of flat shapes and space shapes. There are three geometric shapes found, namely tubes, rhombuses/parallelograms, and circles. and the concept of comparison (ratio) can be seen from the comparison of the production results of various forms of Alu Padeh and Panyaram